Acetate Synthesis from H(2) plus CO(2) by Termite Gut Microbes - Breznak, John A. (1986)
Gut microbiota from Reticulitermes flavipes termites catalyzed an H(2)-dependent total synthesis of acetate from CO(2). Rates of H(2)-CO(2) acetogenesis in vitro were 1.11 ± 0.37 μmol of acetate g (fresh weight)(−1) h(−1) (equivalent to 4.44 ± 1.47 nmol termite(−1) h(−1)) and could account for approximately 1/3 of all the acetate produced during the hindgut fermentation. Formate was also produced from H(2) + CO(2), as were small amounts of propionate, butyrate, and lactate-succinate. However, H(2)-CO(2) formicogenesis seemed largely unrelated to acetogenesis and was believed not to be a significant reaction in situ. Little or no CH(4) was formed from H(2) + CO(2) or from acetate. H(2)-CO(2) acetogenesis was inhibited by O(2), KCN, CHCl(3), and iodopropane and could be abolished by prefeeding R. flavipes with antibacterial drugs. By contrast, prefeeding R. flavipes with starch resulted in almost complete defaunation but had little effect on H(2)-CO(2) acetogenesis, suggesting that bacteria were the acetogenic agents in the gut. H(2)-CO(2) acetogenesis was also observed with gut microbiota from Prorhinotermes simplex, Zootermopsis angusticollis, Nasutitermes costalis, and N. nigriceps; from the wood-eating cockroach Cryptocercus punctulatus; and from the American cockroach Periplaneta americana. Pure cultures of H(2)-CO(2)-acetogenic bacteria were isolated from N. nigriceps, and a preliminary account of their morphological and physiological properties is presented. Results indicate that in termites, CO(2) reduction to acetate, rather than to CH(4), represents the main electron sink reaction of the hindgut fermentation and can provide the insects with a significant fraction (ca. 1/3) of their principal oxidizable energy source, acetate.